Analisis Rasio Likuiditas dan Rasio Aktivitas dalam Meningkatkan Pertumbuhan Laba Pada PT. Siantar Top Tbk. yang Terdaftar di Bursa Efek Indonesia - Arzal Syah; Muh. Abdi Imam; Putri Putri; Rafiqah Asaff; Andi Nurrahma Gaffar (Dinamis : Journal of Islamic Management and Bussiness, 2021)
This study aims to determine and analyze the ratio of liquidity and activity ratios in increasing profit growth at PT Siantar Top Tbk. during 2015-2017. The data collection method used is the method of documentation and literature study. In analyzing the data the author uses quantitative analysis techniques in the form of financial reports listed on the Indonesia Stock Exchange which can be accessed through the official website www.idx.co.id and qualitative techniques. The data processing method used in this study is a non-statistical method, namely by using financial ratio formulas. The results of the analysis of the liquidity ratio and activity ratio of PT Siantar Top Tbk, show that the liquidity ratio for the current ratio in 2015 was 1.58 times, in 2016 it was 1.65 times, in 2017 it was 2.64 times, for the quick ratio in 2015 it was 1 .04 times, in 2016 it was 1.14 times, in 2017 it was 1.81 times. Meanwhile, the cash ratio in 2015 was 1.77%, in 2016 it was 4.44%, in 2017 it was 19.48%. Then the receivable turnover in 2015 was 19.70 times, in 2016 it was 15.84 times, in 2017 it was 28.05 times, for inventory turnover, in 2015 it was 8.52 times, in 2016 it was 9.39 times, in 2017 it was 9 .44 times, for working capital turnover in 2015 it was 2.90 times, in 2016 it was 2.86 times, in 2017 it was 2.98, for fixed asset turnover in 2015 it was 2.53 times, in 2016 it was 2.37, for 2017 was 2.51 times, and total asset turnover in 2015 was 1.32 times, in 2016 was 1.12 times, in 2017 was 1.20 times.